Pharmacognostical Studies and Preliminary Phytochemical Investigations on Roots of Sophora interrupta Bedd., Fabaceae - P. Sai Kumar, S.Sandhya, K.N.V. Rao* and David Banji, Panthati Murali Krishna*, T. Rajeshwar (Journal of Phytology, 2011)
Sophora interrupta Bedd., is a woody perennial shrub which belongs to the family Fabaceae. Many species of this genus like S. flavescens Ait., and S. japonica L. are used in traditional Chinese medicine. Several phytochemical investigations on this genus revealed the presence of many bioactive constituents like matrine and oxymatrine alkaloids, flavonoids, glycosides and polysaccharides which has medicinal importance. In view of its allied species, their importance in the Chinese medicine and in the absence of its scientifically reported pharmacognostical parameters, the present study attempts to undertake the study of qualitative and quantitative microscopic evaluation of the root along with physicochemical parameters and fluorescence analysis of root powder which helps to establish diagnostic characters and quality parameters for the identification of powdered form of root. Phytochemical evaluation of roots revealed the presence of flavonoids, alkaloids, saponins, glycosides and carbohydrates. TLC and HPTLC profile of Benzene extract was performed for flavonoids.